PENINGKATAN KEPUASAN KONSUMEN PADA UMKM MELALUI KOMUNIKASI PEMASARAN, KOMITMEN PENANGANAN KELUHAN DAN KUALITAS PRODUK DI KABUPATEN BANJARNEGARA - Siti Maesaroh; Walid Rudianti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The Covid-19 outbreak has an impact on the global economy, one of which is the Indonesian economy. Micro, Small and Medium Enterprises (MSMEs) are one of the sectors most affected, MSME actors feel that there is a decline in sales due to consumer dissatisfaction caused by sub-optimal marketing communications, commitment to handling complaints that have not been maximized due to constraints on social distancing and quality. product, the purpose of this study was to determine whether there is an effect of marketing communication, commitment to handling complaints and product quality on customer satisfaction.This research was conducted in the city of Banjarnegara with a sample of 200 respondents, distributing questionnaires with a random method. The analytical method used in this research is descriptive statistics with quantitative research type, classical assumption test, there are normality, heteroscedasticity and multicollinearity tests and regression tests, while to test the hypothesis in this study using T and F tests.The results of this study indicate that the variables of marketing communication, commitment to handling complaints and product quality have an effect on customer satisfaction both partially and simultaneously.